Final-year student nurses' experiences of caring for patients - Sewela C. Kobe; Charlene Downing; Marie Poggenpoel (AOSIS, 2020)
Background: Shortage of nurses in South African hospitals has affected the nurse-patient ratio, thus prompting nurses to be focussed on completing nursing-related duties with less or no caring for the patient. Caring involves having a therapeutic relationship with the patients, and it can be challenging and demanding for final-year student nurses who are still novices in the nursing profession. Objectives: To explore and describe the experiences of caring for patients amongst final-year student nurses in order to develop and provide recommendations to facilitate caring. Method: A qualitative, descriptive and contextual design was used. Data collection was done through eight in-depth individual interviews. Giorgi's five-step method of data analysis was used, along with an independent coder. Measures to ensure trustworthiness and ethical principles were applied throughout the research. Results: Four themes with 12 subthemes emerged from the data: therapeutic relationship with patients as an integral part of caring, teamwork - team spirit makes caring easy, continuous caring that promotes quality and safe nursing, as well as satisfaction amongst staff and patients, and various barriers that contributed to lack of caring in the unit. Conclusion: The majority of student nurses had positive experiences of caring, which included therapeutic relationships between nurses and the patients, teamwork and team spirit that fostered safe and quality nursing care, rendered effortlessly. Barriers to caring were also highlighted as negative experiences.